From privilege to competition : unlocking private-led growth in the Middle East and North Africa - Benhassine, Najy (MENA development report., 2009)
The future prosperity of most people of the Middle-East and North Africa--and the social cohesion of their countries--rests in great part on the ability of governments to enable the private sector to respond to this job creation challenge. This is what this report is about. It is about enabling the new generations of entrepreneurs that have emerged over the past years all across the region to play a bigger role in the growth of their countries. It is also about encouraging more investors to believe in the prospects of the region and trusting that business-friendly policy reforms will benefit the.